The Validity and Reliability of The Environmental Awareness Assessment Scale for 48-66 Months Children - Füsun Kurt GÖKÇELİ; Adalet KANDIR (Hacettepe University, 2016)
Objectives: This research was conducted in order to test the validity, reliability of "Environmental Awareness Assessment Scale for 48-66 Months Children". Materials and Methods: The study group of the research consisted of 365 children determined by simple random sampling path from six independent kindergarten tied to Eskisehir Province National Education Directorate in the Central District in Eskişehir. The reliability and validity study of "Environmental Awareness Assessment Scale for 48-66 Months Children" was conducted with the determined study group. The basic premise of the research data was collected via "Personal İnformation Form", "Environmental Awareness Assessment Scale for Children 48-66 Months". Results: For the validation study of Scale, content validity of the scale was evaluated. In order to determine the construct validity of the scale, exploratory factor analysis (EFA), confirmatory factor analysis (CFA) were performed. In order to test the reliability of the scale KR-20 reliability coefficient was calculated. Conclusion: The results were statistically adequate, it was accepted that the scale is valid and reliable.